2021
DOI: 10.1055/s-0041-1731828
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Genetic Testing for Aneuploidy: Current Perspectives

Abstract: Despite improvements in assisted reproduction techniques (ARTs), live birth rates remain suboptimal, particularly in women with advanced maternal age (AMA). The leading cause of poor reproductive outcomes demonstrated in women with AMA, as well as women with recurrent miscarriage and repetitive implantation failure, is thought to be due to high rates of embryonic aneuploidy. Preimplantation genetic testing for aneuploidies (PGT-A) aims to select an euploid embryo for transfer and therefore improve ART outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…1, and were excluded from the study. The most common reasons for exclusion were that the article concerned a conference abstract [13][14][15][16][17][18][19], absence of relevant inclusion criteria , absence of published study results [50,51], absence of a control group [52][53][54][55][56][57][58][59][60][61][62][63], and some studies [64][65][66][67][68] were review articles.…”
Section: Resultsmentioning
confidence: 99%
“…1, and were excluded from the study. The most common reasons for exclusion were that the article concerned a conference abstract [13][14][15][16][17][18][19], absence of relevant inclusion criteria , absence of published study results [50,51], absence of a control group [52][53][54][55][56][57][58][59][60][61][62][63], and some studies [64][65][66][67][68] were review articles.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for poor reproductive outcomes in patients with advanced maternal age, recurrent abortion and repetitive implantation failure is believed to be the high incidence of embryo aneuploidy [22] . One study showed that a PGT-A diagnosis of uniform aneuploidy provides a 98% predictive value for early lethality and a 86.3% miscarriage rate [23] .…”
Section: Discussionmentioning
confidence: 99%
“…This technique is particularly important as a screening test for preimplanted embryo investigation, as it is a noninvasive tool for embryo assessment, avoiding the harmful consequences that may be derived from the invasive manipulations of embryos and could disturb normal development. 24…”
Section: ■ Experimental Sectionmentioning
confidence: 99%